2019
DOI: 10.1007/s13311-019-00753-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the miR-34a-Mediated SIRT1/mTOR Signaling Pathway by Urolithin A Attenuates d-Galactose-Induced Brain Aging in Mice

Abstract: Despite tremendous advances in modern medicine, effective prevention or therapeutic strategies for age-related neurodegenerative diseases such as Alzheimer's disease (AD) remain limited. Currently, accumulating evidence has demonstrated that microRNAs (miRNAs) are increasingly associated with age-related diseases and are emerging as promising therapeutic targets. Urolithin A, a metabolite compound resulting from the transformation of ellagitannins by gut bacteria, has been reported to have anti-oxidant, anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 41 publications
4
115
0
3
Order By: Relevance
“…The in vivo D-galactose-induced brain aging model showed that urolithin A significantly suppressed the upregulation of miR-34a induced by D-galactose. The overall conclusion was that urolithin A may have neuroprotective effects, especially in preventing D-gal-induced brain aging through the activation of the miR-34a-mediated SIRT1/mTOR signaling pathway [53].…”
Section: Urolithin Activity In the Modulation Of Oxidative Stressmentioning
confidence: 99%
“…The in vivo D-galactose-induced brain aging model showed that urolithin A significantly suppressed the upregulation of miR-34a induced by D-galactose. The overall conclusion was that urolithin A may have neuroprotective effects, especially in preventing D-gal-induced brain aging through the activation of the miR-34a-mediated SIRT1/mTOR signaling pathway [53].…”
Section: Urolithin Activity In the Modulation Of Oxidative Stressmentioning
confidence: 99%
“…glucose deprivation, cytoprotective drugs and genetic suppression of inflammasome activity) act to simultaneously up-regulate SIRT1/PGC-1α and suppresses the Akt/mTOR pathway. 20 , 91–93 Furthermore, drugs that act to directly up-regulate SIRT1 (e.g. resveratrol and SIRT1 activators) also serve to inhibit Akt/mTOR, 85 , 94–98 and conversely, suppression of SIRT1 leads to up-regulation of Akt/mTOR.…”
Section: Sirt1 and Akt/mtor Signalling In The Regulation Of Organismamentioning
confidence: 99%
“…Uro-A regulates the expression of intercellular adhesion factor-1 via the ERK/peroxisome proliferator activated receptor-γ signaling pathway, which exerts anti-inflammatory effects (39). Uro-A also induces mitophagy, prolongs the lifespan of Caenorhabditis elegans and increases muscle function in rodents (40,41). In the present study, it was speculated that uro-A was the active component that induced the antioxidant effect of cassia seeds (12,42).…”
Section: Discussionmentioning
confidence: 70%